2016
DOI: 10.1016/j.bjhh.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

l-Amino acid oxidase isolated from Calloselasma rhodostoma snake venom induces cytotoxicity and apoptosis in JAK2V617F-positive cell lines

Abstract: BackgroundMyeloproliferative neoplasms are Philadelphia chromosome-negative diseases characterized by hyperproliferation of mature myeloid cells, associated or not with the Janus kinase 2 tyrosine kinase mutation, JAK2V617F. As there is no curative therapy, researchers have been investigating new drugs to treat myeloproliferative neoplasms, including l-amino acid oxidase from Calloselasma rhodostoma snake venom (CR-LAAO), which is a toxin capable of eliciting apoptosis in several tumor cell lines.ObjectiveTo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…The present findings are in agreement with several LAAO studies from various snake species induced apoptosis in human cancer cell lines such as HeLa [21,45], MM6 [46], Jurkat cells [47] and RBR 17T (human malignant glioma cells) [48]. Moreover, the activation of caspase enzymes, such as caspase-3, was attributed to cancer cell lines, such as SET-2 and CML cells when exposed to CR-LAAO [30,31]. Besides caspase-3, Bcl-2 is an important indicator of apoptosis induction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are in agreement with several LAAO studies from various snake species induced apoptosis in human cancer cell lines such as HeLa [21,45], MM6 [46], Jurkat cells [47] and RBR 17T (human malignant glioma cells) [48]. Moreover, the activation of caspase enzymes, such as caspase-3, was attributed to cancer cell lines, such as SET-2 and CML cells when exposed to CR-LAAO [30,31]. Besides caspase-3, Bcl-2 is an important indicator of apoptosis induction.…”
Section: Discussionsupporting
confidence: 92%
“…CR‐LAAO demonstrated cytotoxic activity against yeast, HL‐60 (human promyelocytic leukaemia cells) and HepG2 (hepatocarcinoma) cell lines . Moreover, the toxin was capable of inducing apoptosis in HEL 92.1.7 (human bone marrow erythrol), SET‐2 (human megakaryoblastic leukaemic cells) and CML (chronic myeloid leukaemia) cells . However, cytotoxic and apoptotic activities of CR‐LAAO in human colon cancer cells have not been reported.…”
mentioning
confidence: 99%
“…Recently, Tavares et al (2016) observed the induction of cytotoxicity by L-amino acid oxidase activity from the venom of Calloselasma rhodostoma species in bone marrow erythroleukemia cell lines (HEL92.1.7 cells) and megakaryoblastic leukemia (Set-2 cells) [27]. Other studies with adenocarcinoma cell lines of human colon LS174 (p53wt), HCT116 (p53wt), and HT29 (p53mut) found that Lebein (disintegrin heterodimeric) isolated from the venom of Macrovipera lebetina snake significantly inhibited cell viability [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BpirLAAO-I induced apoptosis and potentiated the tyronise kinase inhibitor effect on BCR-ABL + cells. Additionally, Tavares et al [8] reported an L-amino-acid oxidase from C. rhodostoma (CR-LAAO) snake venom as a potential antineoplastic agent against HEL 92.1.7 and SET-2 JAK2V617F cell lines derived from myeloproliferative neoplasm patients. Moreover, the cytotoxins CT1 and CT2 from Naja oxiana , CT3 from Naja kaouthia and CT1 from Naja haje showed an important cytotoxicity, mainly mediated by lysosome rupture, against lung adenocarcinoma A549 and promyelocytic leukemia HL60 cells [9].…”
Section: Introductionmentioning
confidence: 99%